The Epistemological Foundations of Music Piracy in the Digital Marketplace - Clayton Davies; Glenn Parry; Janet Carruthers; Marcus Kepple-Palmer (Foresight and STI Governance)
This paper examines the fundamental epistemological gap between the consumers and producers of digitally based products. Using the music industry and the significance of digital products in this arena as a case study of evolving relationships between buyers and sellers, we evaluate the nature of ‘piracy’ from multiple perspectives: creators, intermediaries, distributors, and end consumers. Our study centres on the epistemological boundaries of these agents and actors, using existing evidence and qualitative research to examine the nature and limits of the epistemological reach of agents and actors in this digital marketplace. Our theoretical model is an adapted and applied version of Domain-Generality and Domain-Specificity in Personal Epistemology. We find a series of epistemological dissonances, driven by differing levels of understanding about (and access to) the underlying technological, legal, and social structures of an evolving marketplace. As a result of instability, these structures inevitably create various epistemological boundaries. Using the analytical framework developed, the case study of music piracy illustrates how identifying epistemological dissonance helps sellers develop strategies that could minimize the impact of piracy on their revenue streams.